Revolutionizing Tetracycline Hydrochloride Remediation: 3D Motile Light‐Driven MOFs Based Micromotors in Harsh Saline Environments - Yu Zhao; Jiawei Lin; Qing Wu; Yulong Ying; Josep Puigmartí‐Luis; Salvador Pané; Sheng Wang (Advanced Science)
Abstract Traditional light‐driven metal‐organic‐frameworks (MOFs)‐based micromotors (MOFtors) are typically constrained to two‐dimensional (2D) motion under ultraviolet or near‐infrared light and often demonstrate instability and susceptibility to ions in high‐saline environments. This limitation is particularly relevant to employing micromotors in water purification, as real wastewater is frequently coupled with high salinity. In response to these challenges, ultrastable MOFtors capable of three‐dimensional (3D) motion under a broad spectrum of light through thermophoresis and electrophoresis are successfully synthesized. The MOFtors integrated photocatalytic porphyrin MOFs (PCN‐224) with a photothermal component made of polypyrrole (PPy) by three distinct methodologies, resulting in micromotors with different motion behavior and catalytic performance. Impressively, the optimized MOFtors display exceptional maximum velocity of 1305 ± 327 µm s−1 under blue light and 2357 ± 453 µm s−1 under UV light. In harsh saline environments, these MOFtors are not only maintain high motility but also exhibit superior tetracycline hydrochloride (TCH) removal efficiency of 3578 ± 510 mg g−1, coupling with sulfate radical‐based advanced oxidation processes and peroxymonosulfate. This research underscores the significant potential of highly efficient MOFtors with robust photocatalytic activity in effectively removing TCH in challenging saline conditions, representing a substantial advancement in applying MOFtors within real‐world water treatment technologies.